The Effect Of Green Training On Corporate Sustainable Performance With Green Transformational Leadership As a Moderating Variable At PT. Angkasa Pura Indonesia, Pekanbaru City Branch Office - Galih Vidia Anggreani; Kurniawaty Fitri; Mida Aprilina Tarigan (Westscience Press, 2025)
This study aims to analyze the effect of green training on corporate sustainable performance, as well as the role of green transformational leadership as a moderating variable at PT. Angkasa Pura Indonesia Pekanbaru Branch Office. This study uses a quantitative approach with a questionnaire distribution method. The population in this study are employees at PT. Angkasa Pura Indonesia Pekanbaru Branch Office, with a sampling technique using Proportional Stratified Random Sampling. The data were analyzed using a moderation regression test with the help of SPSS 27. The results showed that green training had a partial positive and significant effect on corporate sustainable performance. In addition, green transformational leadership was proven to moderate this effect.